The Analysis of the Impact of the Open Unemployment Rate (TPT) and Economic Growth on the Human Development Index in Kabupaten Kerinci - Rosi, Adek Irma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to determine and analyze whether there is an influence between the open unemployment rate and economic growth on the human development index in Keinci Regency. This research is quantitative research using secondary data originating from the Central Statistics Agency (BPS) with panel data which is time series data for the 2014-2023 period. The data analysis method uses multiple linear regression analysis. The research results show that partially and simultaneously there is a significant influence between the open unemployment rate and economic growth on the human development index in Kerinci Regency. The magnitude of the influence of the open unemployment rate and economic growth on the Kerinci Regency human development index simultaneously on the human development index is 94.4% and the remaining 5.6% is influenced by other factors outside this research.